Hubungan Dukungan Penghargaan Suami Dengan Kejadian Anemia Pada Ibu Hamil - Teti Rahmawati (STIKes Persada Husada Indonesia, 2016)
Expectant mothers and families health attitude can influence the occurrence of anemia in expectantmothers. However, it is not known yet the husbands’ support influence towards the occurrence of anemia inexpectant wives. This study aimed to identify support recognition influencing occurrence of anemia in expectantmothers. This analytic descriptive study uses cross sectional approach and was carried out at Sector Sukatani,Sub-District Tapos, Depok between January- June 2015 towards 60 expectant mothers selected by total sampling.Data collected utilized questionaires on respondents’ perception towards knowledge, attitude and husbands’support behavior related to anemia. Hb tests used multicheck units to obtain respondents Hb data. Study result showed a significant relationship between husbands’ recognition support with anemia occurrence in expectantmothers (p value = 0,021). Expectant mothers lacking husbands’ recognition support has a higher chance 4,680times of experiencing anemia compared to expectant mothers with good husbands’ recognition support (OR = 4,680). Requires early anemia detection policy through Hb screening, health promotion administration, conducting care and services involving husbands and further studies related to recognition support through perspective husbands.